Analisis Faktor – Faktor Yang Mempengaruhi Income Smoothing Pada Perusahaan Sektor Barang Konsumsi - Marcellino, Marcellino; Iskak, Jamaludin (Jurnal Paradigma Akuntansi, 2024)
The purpose of this study was to obtain empirical evidence of the influence of profitability, leverage, cash holding, and dividend payout ratio on income smoothing. The subjects in this study were manufacturing companies in the consumer goods sector listed on the Indonesia Stock Exchange for the period 2016 – 2019. The population in this study amounted to 56 companies and after being selected using the purposive sampling method, the research sample consisted of 19 companies where for four periods, the number of data became 76. Eviews version 12.0 program was used for data processing. The results of research on profitability had no effect on income smoothing, leverage had no effect, cash holding had a significant positive effect, while dividend payout ratio had no effect on income smoothing. The implication of this study is that stable profitability and leverage are needed to reduce income smoothing actions which will provide a good signal for investors.